Factors Associated with Modern Contraceptive Use among Married Women Attending Comprehensive Health Centers (CHCs) in Kandahar, Afghanistan. (7th April 2021) - Saheem, Mirwais; Stanikzai, Muhammad Haroon; Rahimy, Najeeb; Fazli, Najibullah; Mudasir, Ghulam Mohydin; Sayam, Hadia
Abstract : Background . Modern contraceptives are highly effective and reliable methods of preventing unintended pregnancies and reducing maternal deaths. Only 22 percent of currently married women use modern methods of contraceptives in Afghanistan. This study assessed the factors associated with modern contraceptive use among married women attending comprehensive health centers (CHCs) in Kandahar Province. Methods . This was an institution-based cross-sectional study that included 325 married women who attended randomly selected comprehensive health clinics in Kandahar between September and October 2019. The total sample size was allocated proportionally to selected health clinics based on the recent 3-month average patients load. We used a consecutive sampling method to select study participants. Data were collected in a structured questionnaire, which included information on respondents' demographic, socioeconomic, reproductive, and contraceptive experiences. Data was analyzed using SPSS 21.00 statistical software. We used descriptive statistics such as tables and proportions to present data. Binary and multiple logistic regression analyses were carried out to determine factors associated with modern contraceptive use. Results . Out of 325 married women, 127 used modern contraceptives with a prevalence of 39.1% (95 % CI = 33.7 % –44.6%). The results indicated that the area of residence (AOR = 2.61, 95% CI 1.43-4.78) and ever use of contraceptives (AOR = 14.92, 95% CI 6.88-32.34) are associated with modern contraceptive use among married women attending comprehensive health centers in Kandahar. Conclusion . This study found that modern contraceptive use was higher than reported on the national level. The most persistent factors associated with modern contraceptive use in this study were urban residence and ever use of contraceptives. As a policy measure, family planning programs should be prompted to the rural residency in Kandahar Province.